An Evolutionary Framework for Developed Country-Developing Country Co-Operation for the Development of Environment and Natural Resources Data-Banks - Seshagiri, N.; Agnihotry, A. P. (Journal of Information and Knowledge, 1978)
Analyses the specific problems relating to the design, development and applications of natural resources and environment data banks in developing countries. An evolutionary framework is proposed which is likely to derive maximum benefit from the state-of-the-art developed and the experience gained in developed countries while keeping in view the special problems and requirements of developing countries. Based on this frame-work, a modality is suggested for exchange of information, methodologies and experience between a typical developing country and a typical developed country. A few specific areas for cooperation between India and USA in the area of computerised information system are suggested.